The Evaluation of Interactive Snakes Impact and Ladders Game on Increasing Tutor Creativity at Jelita PAUD, Palangka Raya City - Desi Eyunike Br Bangun; Hendrowanto Nibel (Budapest International Research and Critics University, 2022)
This evaluation brtujuan to know 1) the results of evaluation of the impact of snake and ladder games on improving the creativity of tutors in PAUD JELITA Palangka Raya City. 2) To know the understanding of tutors in PAUD JELITA about the importance of media in learning early childhood. This research is a descriptive study with a qualitative approach. The subjects of the study were principals and tutors in paud jelita, a single hill village, palangka raya city. Method of data collection with observation, interview and documentation. Data analysis techniques used are data reduction, data presentation, and verification. Triangulation is done to explain data freedom using sources. The results showed that: (1) evaluation of the impact of interactive snakes and ladder games conducted, first verifying prospective students, then tutors and organizers identifying the needs of students, then tutors compiling the teaching materials needed. (2) The tutor's understanding of the importance of media in early childhood learning, the researchers found that the understanding of tutors in the evaluation of the impact of snakes and ladders was very influential in the motivation of the students. Understanding is something we understand and we understand properly. Similarly, tutors in paud beautiful who are expected to be able to understand and apply the game of snakes and ladders to increase the spirit of learning learners. Tutors are obliged to always innovate so that learning attracts more students. Tutors always have a new creativity, can use something to look attractive and can increase the interest or motivation of learning students.